2011
DOI: 10.1002/ajmg.b.31231
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of the 3q29 microdeletion syndrome candidate genes DLG1 and PAK2 in schizophrenia

Abstract: Deletion of chromosome 3q29, which is associated with mental retardation and autism, was recently identified as being present in excess or occurring de novo in schizophrenia cases, being present in approximately 1/1,000 cases and 1/40,000 unscreened controls. Of the ∼20 genes in the commonly deleted region two are prominent candidates for involvement in the behavioral features of the microdeletion syndrome: DLG1 and PAK2. We report the result of mutation screening of the entire protein coding sequence of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 40 publications
(52 reference statements)
2
34
0
2
Order By: Relevance
“…Although numerous studies have shown expression level changes and genetic association between other PSD genes and schizophrenia [42]–[48], our study failed to detect association between DLG1 , PICK1 and MDM2, and schizophrenia in Japanese cohorts, which is in line with reports for DLG1 [49] and PICK1 [50].…”
Section: Discussionsupporting
confidence: 91%
“…Although numerous studies have shown expression level changes and genetic association between other PSD genes and schizophrenia [42]–[48], our study failed to detect association between DLG1 , PICK1 and MDM2, and schizophrenia in Japanese cohorts, which is in line with reports for DLG1 [49] and PICK1 [50].…”
Section: Discussionsupporting
confidence: 91%
“…Rare DLG1 mutations have been found in patients (11) along with microdeletions that include the DLG1 (16,17) (Table 1) or DLG2 (18) gene. This supports the overall concept of glutamate synapse/signalling dysfunction in schizophrenia, and drugs targeted at facilitating NMDA-R function have so far proved mildly promising (S12).…”
Section: Ligand-gated Ion Channel Receptorsmentioning
confidence: 99%
“…Despite this complication, small CNVs represent a promising avenue for future studies with sufficiently powered study populations (both in sample size and resolution) and parental cases for determining de novo status. Specific examples of small CNVs are beginning to arise in genome-wide studies, such as VIPR2 duplications in schizophrenia, partial TMLHE deletions in autism, a collection of significant events in ID/DD subtypes, and events overlapping with genes identified to contain de novo mutations and indels [Boone et al, 2010;Celestino-Soper et al, 2011;Cooper et al, 2011;Kirov et al, 2011;Vacic et al, 2011].…”
Section: Cnv Landscape Of Neuropsychiatric and Neurodevelopmental Conmentioning
confidence: 99%
“…Recently, Carroll et al, [2011] identified rare mutations in one gene (DLG1) highlighting its potential involvement in the schizophrenia phenotype. The variability in expression is further supported by a case report of a child with autistic features, an elongated face, and normal IQ [Cobb et al, 2010].…”
Section: Variable Expressivity Of Specific Locimentioning
confidence: 99%